The impact of anions on electrooxidation of perfluoroalkyl acids by porous Magnéli phase titanium suboxide anodes - Yaye Wang; Yifei Wang; Shuping Dong; Qingguo Huang (PLoS ONE, 2025)
Previous studies have indicated the great performance of electrooxidation (EO) to mineralize per- and polyfluoroalkyl substances (PFASs) in water, but different anions presented in wastewater may affect the implementation of EO treatment in field applications. This study invetigated EO treatment of perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), two representative perfluoroalkyl acids (PFAAs), using porous Magnéli phase titanium suboxide anodes in electrolyte solutions with different anions present, including NO3-, SO42-, CO32- and PO43-. The experiment results indicate that CO32- enhanced PFAS degradation, while NO3- suppressed the degradation reactions with its concentration higher than 10 mM. SO42- and PO43- exhibited less impact. Further studies with electrochemical characterizations and radical quenching experiments illustrate the mechanisms of how the anions may impact EO performance.